2013
DOI: 10.3311/pptr.7111
|View full text |Cite
|
Sign up to set email alerts
|

Effect of heat treatment on fracture surfaces in recycled aluminium cast alloy

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…However, the addition of magnesium caused the AlSi12 alloy to absorb much lower energy. These results are similar to the different studies reported in the previous literature (Hurtalová et al , 2013; Morin et al , 2016). It is believed that the magnesium-containing alloys absorb less energy in the tensile test and less energy in the impact test because of the brittle Mg 2 Si in their structure compared to the AlSi12 alloy.…”
Section: Resultssupporting
confidence: 93%
“…However, the addition of magnesium caused the AlSi12 alloy to absorb much lower energy. These results are similar to the different studies reported in the previous literature (Hurtalová et al , 2013; Morin et al , 2016). It is believed that the magnesium-containing alloys absorb less energy in the tensile test and less energy in the impact test because of the brittle Mg 2 Si in their structure compared to the AlSi12 alloy.…”
Section: Resultssupporting
confidence: 93%
“…Metallographic samples (2 cm x 1.5 cm) were sectioned from the casted test bars and standard prepared for metallographic observations such as -wet ground on SiC papers, DP polished with 3 μm diamond past followed by Struers Op-S, etched by 0.5 % HF or H 2 SO 4 (for helping the highlighting of Fe-intermetallic phases) . Some samples were also deep-etched for 30 s in HCl solution in order to reveal the three-dimensional morphology of the silicon phase (Hurtalová et al, 2013). The specimen preparation procedure for deep-etching consists of dissolving the aluminium matrix in a reagent (36 % HCl) that will not attack the eutectic components or intermetallic phases.…”
Section: Methodsmentioning
confidence: 99%
“…This is a considerable advantage in modern metallurgical industry. For the past 20 years the proportion of metal consumed that is recycled has grown steadily and today stands at something like 30 % of primary metal production (European Aluminium Association; Schlesinger, 2014;Hurtalová et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The second step is water quenching at 40 °C and the third step is artificial aging at temperature 170 °C with holding time 4 hours, where solute atoms precipitate. These heat treatments were specified as optimum for secondary AlSi9Cu3 cast alloy at many previous studies [15][16][17][18].…”
Section: Experimental Workmentioning
confidence: 99%